2020
DOI: 10.3390/su12198203
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Modified and Unmodified Natural Clay Deposits for In Situ Immobilization and Reducing Phytoavailability of Molybdenum in a Sandy Loam Calcareous Soil

Abstract: Molybdenum (Mo) in basic soils has high bioavailability and plant toxicity. This study aimed to investigate the effect of increasing Mo concentration on its availability and toxicity threshold in alfalfa plants grown in sandy loam calcareous soils, and the potential use of raw and acid- modified clay deposits as soil additives to immobilize Mo and reduce its phytoavailability. Raw clay deposits (RCD) were treated with H2SO4 to produce acid-modified clay deposits (AMCD). The first experiment was performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In sandy soil, ammonium is also poorly retained the negative charges in the soil (Alrashidi et al, 2020) due to the low clay and MO content usually found in these soils, which also increases the possibility of losses in this chemical form. Soil texture is, therefore, an essential factor in the behavior of N because it directly influences the dynamics of water in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…In sandy soil, ammonium is also poorly retained the negative charges in the soil (Alrashidi et al, 2020) due to the low clay and MO content usually found in these soils, which also increases the possibility of losses in this chemical form. Soil texture is, therefore, an essential factor in the behavior of N because it directly influences the dynamics of water in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The increased pyrolysis temperature enhances the tensile strength of the raw materials, resulting in biochar particles that are smaller in size (Albalasmeh et al 2020;Ahmed et al 2021;Wani et al 2022). The functional groups on the ionic charges, surface, and porous structure of biochar aid in the detoxification (Alrashidi et al 2020), physical adsorption (Zhang et al 2020a), complexation, mobilization-immobilization (Hu et al 2020), and co-precipitation (Deng et al 2019) of metal pollutants and support phytoremediation potential of the hyperaccumulator. The physical and chemical characteristics of biochar produced from several feedstocks are displayed in Table 3.…”
Section: Concerns About Biochar In the Environmentmentioning
confidence: 99%
“…Due to the improved tensile strength of raw materials at higher pyrolysis temperatures, it may yield smaller-sized biochar particles ( Albalasmeh et al, 2020 ). The functional groups on the surface of biochar, porous structure, and ionic charges can aid in the physical adsorption ( Zhang et al, 2020 ), co-precipitation ( Chen et al, 2022 ), complexation, mobilization/immobilization ( Hu et al, 2020 ), and detoxification ( Alrashidi et al, 2020 ) of metal pollutants and support the hyperaccumulator’s phytoremediation potential.…”
Section: Biochar Propertiesmentioning
confidence: 99%